The impact of export market orientation on SME market performance: Exploring the moderating effect of government policy and the mediating effect of information access - Sunday Noya; Stefanus Yufra M. Taneo; Melany (Problems and Perspectives in Management)
This study addresses the relevance of export market orientation in enhancing the market performance of small and medium-sized enterprises (SMEs), specifically examining the moderating role of government policy and the mediating effect of information access. The paper aims to provide insights into how these factors collectively impact SME performance. Data were collected from members of the Malang Regency SME Communication Forum, chosen for their relevance as active players in one of Indonesia’s regions with the highest SME concentration. An online questionnaire was used to gather insights directly from the business owners and managers, yielding 448 valid responses that provide a representative perspective on SME market dynamics. The collected data were then analyzed using structural equation modeling (SEM) techniques. The findings demonstrate that export market orientation significantly boosts SME market performance (path coefficient = 0.512, p < 0.001), highlighting its critical role in fostering customer-oriented practices and adaptive marketing strategies. Additionally, export market orientation positively influenced information access (path coefficient = 0.359, p < 0.001), facilitating timely market insights that support decision-making. However, the mediating effect of information access on the relationship between export market orientation and market performance was not statistically significant (path coefficient = 0.242, p = 0.072). Furthermore, the strengthening effects of government policy on both export market orientation and market performance and on export market orientation and information access were also insignificant (path coefficients = –0.103 and 0.053, p = 0.053 and 0.132, respectively). AcknowledgmentWe thank the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia for funding this investigation through a decentralized grant for the Higher Education Fundamental Research scheme for the 2024 fiscal year.